1 1 + 2 1
The above expression can be expressed as b a + d c , where a , b , c and d are positive integers with g cd ( a , b ) = g cd ( c , d ) = 1 . Find a + b + c + d .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The presentation of this solution makes it seem "magical". In actuality, we are simply interested in rational numbers α , β which satisfy
α + β = 1 1 , α × β = 2 2 1 .
Nice!! .I was thinking the same(removing square root) but unable to do.
Did the same
1 1 + 2 1 2 = b a + d c + 2 b d a c
b d a d + b c = 1 1
4 b d a c = 2 1
From the last equation we see that bd must be a multiple of 4. Since we can choose 2 variables free we take b=1 and d=4 following:
a c = 2 1
a + 4 c = 1 1
Calculating a=1/2 and c=42 we may write: 2 1 + 4 4 2 = 2 1 + 2 2 1 resuting in the solution 2 6 .
Yes I do such problem just as per Challenge Master note for Nihar Mahajan .
X
+
Y
=
1
1
,
X
∗
Y
=
2
2
1
.
S
o
X
=
2
2
1
,
Y
=
2
1
.
a+b+c+d=21+2+1+2=26.
We want to express 1 1 + 2 1 as b a + d c
Now, let b a = p and d c = q
1 1 + 2 1 = p + q 1 1 + 2 1 = ( p + q ) 2 1 1 + 2 1 = p 2 + q 2 + 2 p q
We know that p 2 + q 2 do not have a square root anymore, therefore
p 2 + q 2 = 1 1
which leaves us with
2 p q = 2 1 4 p 2 q 2 = 2 1 q 2 = 4 p 2 2 1
Substitute this to the equation above:
p 2 + 4 p 2 2 1 = 1 1 4 p 4 − 4 4 p 2 + 2 1 = 0 ( 2 p 2 − 2 1 ) ( 2 p 2 − 1 ) = 0 p 2 = 2 2 1 , 2 1 p = ± 2 2 1 , ± 2 1
Now, we know that p = b a can only either be a positive number or a complex number, there are no negative values for p .
Therefore, p = 2 2 1 , 2 1
If p = 2 2 1 , q = 2 1 (Similarly, q cannot have a negative value)
If p = 2 1 , q = 2 2 1
Therefore, 1 1 + 2 1 = p + q = 2 1 + 2 2 1
a = 1 , b = 2 , c = 2 1 , d = 2 . (Or if you simpy insist, a = 2 1 , b = 2 , c = 1 , d = 2 )
a + b + c + d = 1 + 2 + 2 1 + 2 = 2 6
Applying the formula a + b = 2 a + a 2 − b + 2 a − a 2 − b , we get:-
1 1 + 2 1 = 2 1 1 + 1 1 2 − 2 1 + 2 1 1 − 1 1 2 − 2 1 = 2 1 1 + 1 2 1 − 2 1 + 2 1 1 − 1 2 1 − 2 1 = 2 1 1 + 1 0 0 + 2 1 1 − 1 0 0 = 2 1 1 + 1 0 + 2 1 1 − 1 0 = 2 2 1 + 2 1
∴ a + b + c + d = 2 1 + 2 + 1 + 2 = 2 6
Can you please show me how?
a + b = 2 a + a 2 − b + 2 a − a 2 − b
Log in to reply
I have not really yried proving but I have learnt that formula, i will tell it if I get.
Log in to reply
@Nihar Mahajan You know it.
You get it now??
Log in to reply
@A Former Brilliant Member – Square both sides and everything cancels nicely, giving equality.
I did the same way
Log in to reply
Great :) :+1:
Log in to reply
In response to Ashish Siva:Thanks
Log in to reply
@Fidel Simanjuntak – In response to Fidel Simanjuntak: Youre welcome
Problem Loading...
Note Loading...
Set Loading...
1 1 + 2 1 = ( 2 2 1 ) 2 + ( 2 1 ) 2 + 2 2 2 1 2 1 = ( 2 2 1 + 2 1 ) 2 = 2 2 1 + 2 1
Thus a + b + c + d = 2 1 + 2 + 1 + 2 = 2 6